PENGARUH PERTUMBUHAN EKONOMI, KEMANDIRIAN KEUANGAN DAERAH TERHADAP STRUKTUR EKONOMI DAN KESEJAHTERAAN MASYARAKAT PROVINSI BALI - Gunarta, Nyoman Adi; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 3 (2022): VOL 11 NO 3, MARET 2022 [807-1213]DO - 10.24843/EEP.2022.v11.i03.p01, 2022)
One goals of Sustainable Development Goals (SDGs) is achieve community welfare all levels. Although welfare of people Bali Province has increased, increase tends to be low and there is still a disparity in the distribution. This study aims to determine and analyze the effect of regional economic growth and financial independence on the economic structure and welfare of the community. The data used in this study is panel or combined data, which combines time series data from 2012 – 2019 with cross section data, namely 9 districts/cities in Bali Province. Therefore, the number of observation points in this study is 72. The results of the analysis show that: 1) Economic growth and regional financial independence have a positive effect on the economic structure in the Regency/City of Bali Province, 2) Economic structure has a positive and significant impact on the welfare of the community in the Regency/City of Bali Province, 3) Economic growth and regional financial independence has a positive and significant impact on the welfare of the community in the Regency/City of the Province of Bali, 4) Economic growth and regional financial independence have a direct effect on the welfare of the community through the economic structure of the Regency/City of the Province of Bali. Keywords: economic growth, regional financial independence, economic structure, community welfare. JEL Classifications: O40, G38, H11, D60?